2021
DOI: 10.4103/aian.aian_848_20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cerebral Perfusion on Arterial Spin Labeling (ASL) MRI with Brain Volumetry and Cognitive Performance in Mild Cognitive Impairment and Dementia due to Alzheimer's Disease

Abstract: Context: Cerebral blood flow (CBF) measurement using arterial spin labelling (ASL) MRI sequences has recently emerged as a prominent tool in dementia research. Aims: To establish association between quantified regional cerebral perfusion and gray matter (GM) volumes with cognitive measures in mild cognitive impairment (MCI) and early Alzheimer's Dementia (AD), using three dimensional fast spin echo pseudo-continuous ASL MRI sequences. Settings and Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…This study also showed that changes in cognitive function were not associated with changes in CBF 76 . However, some studies have found that the MMSE score of AD patients is correlated with CBF in the right posterior cingulate cortex (PCC), hippocampus and bilateral temporoparietal combined cortical 75,77 . Another study found that CBF in the precuneus and temporal cortex was positively correlated with cognitive function in AD patients, while it was negatively correlated in the hippocampus and middle frontal gyrus, which may also be related to compensation 75 .…”
Section: Progress In Mr Imaging Of Admentioning
confidence: 99%
See 4 more Smart Citations
“…This study also showed that changes in cognitive function were not associated with changes in CBF 76 . However, some studies have found that the MMSE score of AD patients is correlated with CBF in the right posterior cingulate cortex (PCC), hippocampus and bilateral temporoparietal combined cortical 75,77 . Another study found that CBF in the precuneus and temporal cortex was positively correlated with cognitive function in AD patients, while it was negatively correlated in the hippocampus and middle frontal gyrus, which may also be related to compensation 75 .…”
Section: Progress In Mr Imaging Of Admentioning
confidence: 99%
“…Arterial spin labeling ASL is a noninvasive method to quantitatively detect cerebral blood flow (CBF) using arterial water molecules as endogenous tracer. 75 CBF is related to cerebrovascular and neuronal function, and CBF is decreased in AD patients. 76 A meta-analysis showed reduced CBF in precuneus in MCI patients and in broader areas, especially the posterior cingulate and temporal-parietal regions in AD patients.…”
Section: 22mentioning
confidence: 99%
See 3 more Smart Citations